From foraging to farming among present-day forest hunter-gatherers: consequences on diet and health - Dounias, E.; Froment, A. (2011)
Throughout history, forests dwellers have adapted to permanent changes of forest ecosystems that, in essence, are dynamic. Accordingly, they have long served as models of how humans lived when their lifestyles and genetic endowment were complementary. What is now commonly described as the “paleodiet” tends to be put forward as a benchmark for present-day efforts to promote health and prevent nutritional diseases, even in industrialized countries. Although forest ecosystems provide food and medicines to forest dwellers, over the last half-century these ecosystems have undergone unprecedented pressure to make way for economic growth and industrialization, often at the cost of ecological functions that may affect human health, both in short term (i.e. increase in infectious diseases) and long term (incidence of global change). As radical alterations occur such as deforestation, modification of resource availability, and the penetration of cash economies, forest dwellers encounter increasing difficulties in accommodating their socioeconomic, cultural, and political systems, thus impeding their ecological success. Diets and diseases are sensitive indicators of the ecological and cultural costs that former hunter-gatherers currently pay to achieve their share of modernity. This paper exposes the nutritional and epidemiological consequences of the maladaptation of former hunter-gatherers in relation to their recent sedentarization. It is primarily based on case studies carried out among the Baka and Kola Pygmies of Cameroon, and the Tubu Punan of Borneo.